Investigating the relevance of mobile technology adoption on inclusive growth in West Africa - Jeremiah O. Ejemeyovwi; Evans Osabuohien (African Governance and Development Institute (AGDI), 2018)
This paper empirically investigates the role of mobile technology adoption on inclusive growth in 15 West African countries with a view to ascertaining if the positive role of mobile technology adoption on human development as established in other regions holds in West Africa. It used data from World Development Indicators for the period 2004 to 2014, which was estimated with system generalised method of moments (SGMM). The SGMM results show that mobile cell subscription has a statistically insignificant effect on inclusive growth in West Africa which refutes the positive and significant role of mobile technology adoption on inclusive growth. The possible reasons for the results and recommendations are documented in the study.
Keywords: O3; O15; 330; ICT; Inclusive growth; Mobile technology; SGMM